IMPLEMENTASI METODE TILAWATI DALAM MENINGKATKAN KETEPATAN MAKHRAJ HURUF HIJAIYAH PADA ANAK USIA 5–6 TAHUN DI TK ISLAM AL-AZHAR 10 SERANG BANTEN - Asri Maulidia; Fadlullah; Fahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the planning, implementation, and evaluation processes, as well as to analyze the supporting factors, inhibiting factors, and solutions in the implementation of the Tilawati method to improve the accuracy of hijaiyah letter pronunciation (makhraj) in children aged 5-6 years at Al-Azhar 10 Serang Islamic Kindergarten. A descriptive qualitative approach was used, with data collected through interviews, observation, and documentation. The findings show that the Tilawati method successfully improves children's ability to pronounce hijaiyah letters more accurately according to their makhraj through classical and individual approaches, the use of rost rhythm, and the read-listen technique. Assessment is carried out through daily evaluation and munaqosyah to measure children's progress. Supporting factors include teacher competence, good communication with parents, and the availability of learning media, while the inhibiting factors come from children's lack of concentration and parents' negligence in preparing the Tilawati book. The solution applied is to build close collaboration between teachers and parents, provide motivation, guidance, and direct pronunciation correction so that children's makhraj accuracy develops optimally. Keywords: Tilawati method, accuracy of makhraj hijaiyah letters, early childhood.